2010
DOI: 10.1590/s1519-69842010000300017
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of mutagenicity and cytotoxicity of Solanum paniculatum L. extracts using in vivo micronucleus test in mice

Abstract: Solanum paniculatum L. is a plant species widespread throughout tropical America, especially in the Brazilian Savanna region. It is used in Brazil for culinary purposes and in folk medicine to treat liver and gastric dysfunctions, as well as hangovers. Because of the wide use of this plant as a therapeutic resource and food, the present study aimed at evaluating the mutagenic and cytotoxic effects of S. paniculatum ethanolic leaf and fruit extracts using the mouse bone marrow micronucleus test. Our results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 43 publications
0
10
0
1
Order By: Relevance
“…The leaf and fruit extracts of this plant have been previously evaluated by the bone marrow micronucleus test in mice and bacterial SOS Inductest in our laboratory, and the results showed that both assays presented high cytotoxic activity and absence of genotoxicity. 22 In the present study we observed that S. paniculatum ELE and EFE exerted differential effects related to the modulation of micronuclei induction when mice were exposed to MMC. Micronuclei separated from and in addition to the main nucleus of a cell are the results of acentric fragments or lagging chromosomes that fail to incorporate into either of the daughter nuclei during telophase of the mitotic cells.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…The leaf and fruit extracts of this plant have been previously evaluated by the bone marrow micronucleus test in mice and bacterial SOS Inductest in our laboratory, and the results showed that both assays presented high cytotoxic activity and absence of genotoxicity. 22 In the present study we observed that S. paniculatum ELE and EFE exerted differential effects related to the modulation of micronuclei induction when mice were exposed to MMC. Micronuclei separated from and in addition to the main nucleus of a cell are the results of acentric fragments or lagging chromosomes that fail to incorporate into either of the daughter nuclei during telophase of the mitotic cells.…”
Section: Discussionmentioning
confidence: 45%
“…9 Recently, using the in vivo micronucleus test in mice and the phage induction SOS Inductest in bacterial strains, our research team was able to demonstrate the absence of genotoxic activity of S. paniculatum leaf ethanolic extract (ELE) and fruit ethanolic extract (EFE); however, cytotoxicity was demonstrated in both extracts. 22 Plants have been widely used as food and for medicinal purposes in different cultures. Currently, the interest in phytomedicinal products has increased worldwide because they can be used against several illnesses, including cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, evaluation of the genotoxicity and antigenotoxicity of these plant products is extremely important. 5 Phytosterols are triterpenes closely resembling cholesterol in both structure and function. They are insoluble in water, but soluble in organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, using the in vivo micronucleus test in mice and the SOS inductest in bacterial strains, our research team was able to demonstrate the cytotoxic activity as well as the absence of genotoxicity of S. paniculatum leaf and fruit crude extracts (Vieira et al 2010a). Additionally, the antigenotoxicity was demonstrated only in the ethanolic leaf extract (Vieira et al 2010b).…”
Section: Introductionmentioning
confidence: 99%